Multiphoton Microscopy and Interaction of Intense Light Pulses with Polymers - Guay, Jean-Michel (Université d'Ottawa / University of Ottawa, 2011)
The nanoscale manipulation of soft-matter, such as biological tissues, in its native environment has promising applications in medicine to correct for defects (eg. eye cataracts) or to destroy malignant regions (eg. cancerous tumours). To achieve this we need the ability to first image and then do precise ablation with sub-micron resolution with the same setup. For this purpose, we designed and built a multiphoton microscope and tested it on goldfish gills and bovine cells. We then studied light-matter interaction on a hard polymer (PMMA) because the nature of ablation of soft-matter in its native environment is complex and not well understood. Ablation and modification thresholds for successive laser shots were obtained. The ablation craters revealed 3D nanostructures and polarization dependent orientation. The interaction also induced localized porosity in PMMA that can be controlled.
Keywords: Multiphoton Microscopy; Interaction of intense pulses with polymers; light-matter interaction